2011
DOI: 10.1371/journal.pone.0026349
|View full text |Cite
|
Sign up to set email alerts
|

The Minimal Domain of Adipose Triglyceride Lipase (ATGL) Ranges until Leucine 254 and Can Be Activated and Inhibited by CGI-58 and G0S2, Respectively

Abstract: Adipose triglyceride lipase (ATGL) is the rate-limiting enzyme of lipolysis. ATGL specifically hydrolyzes triacylglycerols (TGs), thereby generating diacylglycerols and free fatty acids. ATGL's enzymatic activity is co-activated by the protein comparative gene identification-58 (CGI-58) and inhibited by the protein G0/G1 switch gene 2 (G0S2). The enzyme is predicted to act through a catalytic dyad (Ser47, Asp166) located within the conserved patatin domain (Ile10-Leu178). Yet, neither an experimentally determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 36 publications
4
96
0
Order By: Relevance
“…The C-terminal domain contains a hydrophobic region, which is essential for LD binding. 13,25 PNPLA2 catalyzes the initial step in the breakdown of intracellular TGs 24 and, as expected; PNPLA2-defective patients showed impaired degradation of cytoplasmic TGs. Experimental knockout of PNPLA2 in mice leads to cytoplasmic accumulation of TGs in multiple tissues.…”
Section: Discussionsupporting
confidence: 75%
“…The C-terminal domain contains a hydrophobic region, which is essential for LD binding. 13,25 PNPLA2 catalyzes the initial step in the breakdown of intracellular TGs 24 and, as expected; PNPLA2-defective patients showed impaired degradation of cytoplasmic TGs. Experimental knockout of PNPLA2 in mice leads to cytoplasmic accumulation of TGs in multiple tissues.…”
Section: Discussionsupporting
confidence: 75%
“…Although we found the shortest domain with PLA 2 activity to be Met 1 -Ile 202 (PEDF-R4⌬203-232) (Fig. 4), the reported minimum domain for triglyceride lipase activity is slighter longer (Met 1 -Leu 254 ) (46). Differences in substrate recognition (phospholipids versus triglycerides) and/or in recombinant protein expression and purification optimization (i.e.…”
mentioning
confidence: 79%
“…Nonetheless, our data clearly demonstrate that the C-terminal half of PEDF-R is dispensable for phospholipid substrate accessibility and/or PLA 2 activity. It has also been reported that the triglyceride lipase activity can be activated or inhibited by CGI-58 or G0S2, respectively (46,49,50), and that PEDF-R binds to these two regulator proteins with a yet unknown binding site (46,51). It remains to be determined if these proteins can compete with PEDF for the binding to PEDF-R.…”
mentioning
confidence: 99%
“…The sequence motif containing Thr 372 does not resemble a canonical target for any known kinase. The hydrophobic region is a putative lipid-binding region that has been well known for its role in targeting ATGL to LDs (6,17,23). ATGL mutations have been identified in humans with neutral lipid storage disease characterized by excessive TG deposition in nonadipose tissues and myopathy (8,22).…”
Section: Thrmentioning
confidence: 99%
“…␤-Adrenergic stimulation leads to phosphorylation of perilipin 1 by protein kinase A (PKA) and subsequent translocation of ATGL and HSL to the LD surface (3-5, 7, 24, 26), thereby stimulating lipolysis. Reportedly, the NH 2 -terminal region of ATGL, which contains the proposed catalytic dyad Ser 47 and Asp 166 , is critical for catalytic activity, whereas the COOHterminal region of ATGL controls LD localization (6,22). Although ATGL activation at the LD surface by comparative gene identification-58 (CGI-58) was well studied (9, 10), the exact mechanisms underlying the exclusion of ATGL from LDs in the basal state have remained unclear.…”
mentioning
confidence: 99%